A Review of Research on Job Satisfaction - Cheng, Liyuan (International Journal of Social Sciences and Public Administration, 2024)
This article briefly describes the concept of job satisfaction, its categorization, and the theories related to job satisfaction. And finally, it provides ideas related to the future research direction of job satisfaction.